The lobster tale: an exercise in critical thinking. - Stepanovich, Paul L (Journal of Management Education, 2009)
Professors in management and business are encouraged to incorporate critical thinking as an objective in their courses. "The Lobster Tale" provides an opportunity to engage students in various levels of critical thinking, ranging from a relatively superficial reading to an examination of the deeper, often hidden issues. Using the foundations of critical theory and systems theory, the story draws on economics, social theory, philosophy, and other disciplines to present a simplified version of the complexities found in our global environment. It can be used to supplement a variety of courses in the business curriculum and to encourage students to challenge not only assumptions but also conventional wisdom and, perhaps, knowledge itself. © 2009 The Author(s).
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-736-247-110-079 tex.type: [object Object]
Keywords: Affirmative action; Critical theory; Critical thinking; Systems theory; Tragedy of the commons; dept.mgt

Using system dynamics to illustrate deming’s system of profound knowledge - Stepanovich, Paul L (Total Quality Management & Business Excellence, 2004)
This article presents a systems dynamics model to illustrate some of the aspects of Deming's System of Profound Knowledge. As a pedagogical tool, it would serve as a useful introduction for those new to Deming's ideas. It not only introduces the main parts of his system, but also highlights their interconnectedness. The model environment, an interactive management flight simulator, and the model content combine to provide several learning opportunities. The model uses the assumptions of regression to the mean, the 80:20 Rule, random walks, and learned helplessness to present a theory of how, managers learn to reduce quality in organizations. Those interested in exploring or teaching Deming's System can use the model as a launching point from which to explore the system further. Running the simulation provides an opportunity to identify and challenge assumptions, explore the harmful effects of tampering, examine the fundamental attribution error, develop control charts, and challenge the application of behaviourism in management.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-680-699-761-383 tex.type: [object Object]
Keywords: Deming; Pedagogy; Quality; System dynamics; dept.mgt

Strategic conflict: A systems based pedagogical simulation - Stepanovich, Paul; Mueller, James (International Journal of Social Science and Education, 2017)
The paper describes a pedagogical simulation that allows students to explore strategic goal conflict within the context of systems theory. Systems theory emphasizes, among other things, complexity, non-linear relationships, unintended consequences, time delays, and dynamics. Another important aspect of systems thinking is contextual thinking, where objects or relationships cannot be taken as standalone or absolute, but are critically dependent on system structure and the environment. And while strategic planning has long emphasized the importance of environment, it may be difficult for students to experience or appreciate its importance in the planning process. The simulation provides an experiential exercise for a strategy course. The paper provides a summary of systems thinking and strategic goal conflict, a description of the simulation, teaching notes, and experience with the exercise.
Keywords: dept.mgt; ⛔ No DOI found

AACSB accreditation and possible unintended consequences: A deming view. - Stepanovich, Paul L; Mueller, James; Benson, Dan (The Journal of Education for Business, 2014)
The AACSB accreditation process reflects basic quality principles, providing standards and a process for feedback for continuous improvement. However, implementation can lead to unintended negative consequences. The literature shows that while institutionalism and critical theory have been used as a theoretical base for evaluating accreditation, W. E. Deming's philosophy has not. This article fills that void by examining possible negative consequences in meeting faculty qualification requirements in institutions with a teaching mission. © 2014, Copyright Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-359-118-710-616 tex.type: [object Object]
Keywords: AACSB accreditation; Deming; dept.mgt; profound knowledge